2012
DOI: 10.3340/jkns.2012.52.3.204
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Safety in Pedicle Screw Placement in the Thoracic and Lumbar Spines : Comparison Study between Conventional C-Arm Fluoroscopy and Navigation Coupled with O-Arm® Guided Methods

Abstract: ObjectiveThe authors performed a retrospective study to assess the accuracy and clinical benefits of a navigation coupled with O-arm® system guided method in the thoracic and lumbar spines by comparing with a C-arm fluoroscopy-guided method.MethodsUnder the navigation guidance, 106 pedicle screws inserted from T7 to S1 in 24 patients, and using the fluoroscopy guidance, 204 pedicle screws from T5 to S1 in 45 patients. The position of screws within the pedicle was classified into four groups, from grade 0 (no v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 30 publications
2
51
1
Order By: Relevance
“…Possibly for this reason, Shin et al found no statistically significant difference in operative time and estimated blood loss between navigated and nonnavigated cases. 27 To our knowledge, this is the first in the literature that compares the accuracy and safety of the intraoperative O-arm-assisted system without navigation procedure to conventional fluoroscopy. In our study, intraoperative three-axis view in the imaging screen of the O-arm machine offers better observation for the screw positions, which allows safe and accurate screw placement on the first attempt.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly for this reason, Shin et al found no statistically significant difference in operative time and estimated blood loss between navigated and nonnavigated cases. 27 To our knowledge, this is the first in the literature that compares the accuracy and safety of the intraoperative O-arm-assisted system without navigation procedure to conventional fluoroscopy. In our study, intraoperative three-axis view in the imaging screen of the O-arm machine offers better observation for the screw positions, which allows safe and accurate screw placement on the first attempt.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Extensive literature has been published describing the technique, benefits, and drawbacks of each method, as well as comparisons between different approaches. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] With its increasing use has come a multitude of studies regarding the safety of this technique. Proper screw placement is imperative in order to avoid complications such as CSF leak, and pedicle fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Several retrospective studies have also demonstrated increased pedicle screw accuracy using intraoperative CT-based navigation versus conventional techniques. 16 …”
Section: 11mentioning
confidence: 99%
“…13 Intraoperative CT-based navigation systems have been increasingly used with high accuracy in the thoracolumbar spine. 8,16 Given the greater probability of error in placing pedicle screws in small thoracic pedicles, we retrospectively examined the accuracy of previous screw placements in patients with small thoracic pedicles that had been performed using intraoperative CT-guided navigation. In the present study, we analyze our experience with pedicle screw placements in thoracic pedicles with diameters ≤ 3 mm.…”
mentioning
confidence: 99%